creative class - Grigoryeva, Elena (project baikal, 2019)
The term “creative class” became popular in the current century. But it does not mean that the twentieth century lacked creative people. Yana Lisitsina tells how ultimately individual artists joined the Union of the East‑Siberian district, which in 1930 included the Irkutsk region, Krasnoyarsk district, Buryat‑Mongolian ASSR and Chita district. Leo Salmin makes a good attempt to release the history of Soviet design from “mythological remainders” and to study its heritage from the point of view of “archeological fairness”.